TARIAN CAHAYA DALAM FOTOGRAFI - Dody Doerjanto (SURYA SENI, 2008)
Light Dance in Photography. Light dance is a theme of creation that is based on the art of photography. The photographic technique is done directly  on the stage. Therefore, the capture of the aesthetical moment is determined by intensive observation, time availability, and the perception of the photographer.The purpose is to explore and to present the unique and surprising visual aspect of the dancer’s body movement through photographic technique such as static camera, mobile camera, lenses manipulation and any possible kind of photographic technique.The methods are: (1) tangram and quantum approaches (2) trial and error and (3) observation and lateral thinking. The psychological aspect contributesin capturing a scene. Emotional feeling such as joy, happiness, and motivation mix with fear, depression, and worry. This, in fact, generates  different passion.It seems that the event can cause the greater effect of the quantum leap. Thus all creation became more unique and interesting.The result of shows that the camera capture to ward the light reﬂ ection of the acting dancer can generate new image other than the image of the dancer.The new image can be alike the movement of water, wind, dust, dew, ﬁ re, stone, tree and abstract.Keywords : dance and lightI.   PENDAHULUANA. Latar Belakang Penciptaa